Genetic population dynamics of the critically endangered scalloped hammerhead shark (Sphyrna lewini) in the Eastern Tropical Pacific. Issue 12 (28th December 2022) - Harned, Sydney P.; Bernard, Andrea M.; Salinas‐de‐León, Pelayo; Mehlrose, Marissa R.; Suarez, Jenifer; Robles, Yolani; Bessudo, Sandra; Ladino, Felipe; López Garo, Andrés; Zanella, Ilena; Feldheim, Kevin A.; Shivji, Mahmood S.
Abstract: The scalloped hammerhead shark, Sphyrna lewini, is a Critically Endangered, migratory species known for its tendency to form iconic and visually spectacular large aggregations. Herein, we investigated the population genetic dynamics of the scalloped hammerhead across much of its distribution in the Eastern Tropical Pacific (ETP), ranging from Costa Rica to Ecuador, focusing on young‐of‐year animals from putative coastal nursery areas and adult females from seasonal aggregations that form in the northern Galápagos Islands. Nuclear microsatellites and partial mitochondrial control region sequences showed little evidence of population structure suggesting that scalloped hammerheads in this ETP region comprise a single genetic stock. Galápagos aggregations of adults were not comprised of related individuals, suggesting that kinship does not play a role in the formation of the repeated, annual gatherings at these remote offshore locations. Despite high levels of fisheries exploitation of this species in the ETP, the adult scalloped hammerheads here showed greater genetic diversity compared with adult conspecifics from other parts of the species' global distribution. A phylogeographic analysis of available, globally sourced, mitochondrial control region sequence data ( n  = 1818 sequences) revealed that scalloped hammerheads comprise three distinct matrilines corresponding to the three major world ocean basins, highlighting the need for conservation of these evolutionarily unique lineages. This study provides the first view of the genetic properties of a scalloped hammerhead aggregation, and the largest sample size‐based investigation of population structure and phylogeography of this species in the ETP to date. Abstract : The scalloped hammerhead shark is a Critically Endangered (IUCN Red List), circumglobally distributed species in warm temperate and tropical seas. This species exhibits both periods of restricted movements as well a strong migratory propensity and is known to form iconic, large seasonal aggregations at offshore oceanic islands. In this manuscript, we report on the population genetic dynamics of scalloped hammerheads within the Eastern Tropical Pacific (ETP—a region experiencing high levels of illegal, unreported and unregulated fishing), and the mitochondrial phylogeography of this species worldwide.